Estimation of metal surface roughness using fiber optic displacement sensor - Harun, Sulaiman Wadi; Yasin, M.; Yang, H.Z.; Kusminarto, -; Karyono, -; Ahmad, Harith (IOP Publishing, 2010)
A fiber optic displacement sensor is proposed to estimate the roughness of metal surface using the intensity modulation technique. A light beam is launched onto the metal surface via a bundled fiber. The reflected light from the surface is collected and then routed to a silicon detector. The level of roughness for aluminum, stainless steel and copper samples are estimated to be approximately 27, 26, and 20% respectively by fixing the object within the linear range of the sensor. The output voltages are measured as a function of lateral distance to estimate the roughness of the surface.